Pembuatan Game Adventure 2D Cindelaras Berbasis Android Menggunakan Motion Sensor - Danny Lesmana; Leo Willyanto Santoso; Rudy Adipranata (Jurnal Infra, 2017)
Folklore is stories handed down from time to time which tells the life of a hero, people from ancient times , and variety of Indonesian ancient cultures. Folklore has many benefits by providing good morals for young people or helping to learn the culture in a certain area. But along with the development of technology, cultural traditions in Indonesia began to fade. Ease of obtaining information to make people more interested in following foreign cultures rather than maintain the culture of Indonesia. Folklore also get the impact, causing people prefer find out foreign folklore such as Cinderella, Snow White, Beauty and the Beast, and many more better than finding Indonesian folklore that contain a lot of moral story and ethical values.By way of adjusting to the evolving technologies, this application is easily available in the gadget with the android operating system. The advantage of this application is in addition to tell the story to the people, this application also has mini games that people can play. Several mini games contained in this application uses a sensor in android device which is an accelerometer sensor which serves to capture the acceleration of gadget. This folklore application is an application-based learning with mobile devices designed with Java and compiling assisted by Android Studio.The application development is intended to increase public interest in the Cindelaras folklore and as well as a medium of learning for children about moral and ethical values.